Randomized clinical trial of stapler versus clamp-crushing transection in elective liver resection. Issue 3 (8th January 2014) - Rahbari, N N; Elbers, H; Koch, M; Vogler, P; Striebel, F; Bruckner, T; Mehrabi, A; Schemmer, P; Büchler, M W; Weitz, J
Abstract: Background: Various devices have been developed to facilitate liver transection and reduce blood loss in liver resections. None of these has proven superiority compared with the classical clamp-crushing technique. This randomized clinical trial compared the effectiveness and safety of stapler transection with that of clamp-crushing during open liver resection. Methods: Patients admitted for elective open liver resection between January 2010 and October 2011 were assigned randomly to stapler transection or the clamp-crushing technique. The primary endpoint was the total amount of intraoperative blood loss. Secondary endpoints included transection time, duration of operation, complication rates and resection margins. Results: A total of 130 patients were enrolled, 65 to clamp-crushing and 65 to stapler transection. There was no difference between groups in total intraoperative blood loss: median (i.q.r.) 1050 (525–1650) versus 925 (450–1425) ml respectively ( P = 0·279). The difference in total intraoperative blood loss normalized to the transection surface area was not statistically significant ( P = 0·092). Blood loss during parenchymal transection was significantly lower in the stapler transection group ( P = 0·002), as were the parenchymal transection time (mean(s.d.) 30(21) versus 9(7) min for clamp-crushing and stapler transection groups respectively; P < 0·001) and total duration of operation (mean(s.d.) 221(86) versus 190(85) min; P = 0·047). There were no significant differences in postoperative morbidity ( P = 0·863) or mortality ( P = 0·684) between groups. Conclusion: Stapler transection is a safe technique but does not reduce intraoperative blood loss in elective liver resection compared with the clamp-crushing technique. Registration number: NCT01049607 (http://www.clinicaltrials.gov ). Abstract : Stapler technique does not reduce blood loss